Magnetic fabric study in the Triassic slates of the Tethyan Himalaya (SE Tibet) - Antolín, B.; Appel, E.; Montomoli, C.; Dunkl, I.; Ding, L.; Gloaguen, R. (TRABAJOS DE GEOLOGÍA, 2009)
A study of the anisotropy of magnetic susceptibility (AMS) has been done at 24 sites in theTethyan Himalaya Thrust Belt in SE-Tibet. The sites are located in the Triassic slates. Generally Kminaxes are well grouped at the pole of the mesoscopic foliation. Magnetic foliation strikes WNW-ESEbut shows different dips south and north of the Dalmar fault: it has intermediate dips toward the southin the northern part and intermediate dips to the north in the southern part of the same fault. We presentnew magnetic fabric data to better understand the tectonometamorphic history of SE-Tibet, a keyarea to understand the formation history of the Himalaya-Tibetan Plateau uplift.